Preclinical and clinical evaluation of German-sourced ONC201 for the treatment of H3K27M-mutant diffuse intrinsic pontine glioma. Issue 1 (19th November 2021) - Duchatel, Ryan J; Mannan, Abdul; Woldu, Ameha S; Hawtrey, Tom; Hindley, Phoebe A; Douglas, Alicia M; Jackson, Evangeline R; Findlay, Izac J; Germon, Zacary P; Staudt, Dilana; Kearney, Padraic S; Smith, Nathan D; et al.
Abstract: Background: Diffuse intrinsic pontine glioma (DIPG) is a fatal childhood brainstem tumor for which radiation is the only treatment. Case studies report a clinical response to ONC201 for patients with H3K27M-mutant gliomas. Oncoceutics (ONC201) is only available in the United States and Japan; however, in Germany, DIPG patients can be prescribed and dispensed a locally produced compound—ONC201 German-sourced ONC201 (GsONC201). Pediatric oncologists face the dilemma of supporting the administration of GsONC201 as conjecture surrounds its authenticity. Therefore, we compared GsONC201 to original ONC201 manufactured by Oncoceutics Inc. Methods: Authenticity of GsONC201 was determined by high-resolution mass spectrometry and nuclear magnetic resonance spectroscopy. Biological activity was shown via assessment of on-target effects, in vitro growth, proliferation, and apoptosis analysis. Patient-derived xenograft mouse models were used to assess plasma and brain tissue pharmacokinetics, pharmacodynamics, and overall survival (OS). The clinical experience of 28 H3K27M+ mutant DIPG patients who received GsONC201 (2017–2020) was analyzed. Results: GsONC201 harbored the authentic structure, however, was formulated as a free base rather than the dihydrochloride salt used in clinical trials. GsONC201 in vitro and in vivo efficacy and drug bioavailability studies showed no difference compared to Oncoceutics ONC201. Patients treated with GsONC201 (n = 28) showed a median OS of 18 months ( P = .0007). GsONC201 patients who underwent reirradiation showed a median OS of 22 months compared to 12 months for GsONC201 patients who did not ( P = .012). Conclusions: This study confirms the biological activity of GsONC201 and documents the OS of patients who received the drug; however, GsONC201 was never used as a monotherapy.